2021
DOI: 10.11648/j.ajns.20211003.15
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Efficacy on Cognitive Function in Patients with Acute Stroke: Verification of the Medicating Effect of Family Support

Abstract: Background: Post-stroke cognitive impairment (PSCI) is a common consequence of stroke. Many factors that affect cognitive function are known, but the effects of self-efficacy and family support have not been identified. Objectives: This study was a descriptive correlation investigation to determine the mediating effects of family support on the relationship between self-efficacy and cognitive function in stroke patients. Methods: This descriptive cross-sectional study recruited 339 adult patients with acute st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Studies on chemotherapy patients found that better self-efficacy was associated with better quality of life and lower fatigue [ 11 ]. Confidence in one’s ability to manage oneself well is an important aspect of ongoing care [ 12 ]. Individuals with high self-efficacy after a stroke usually have greater confidence to participate in ADLs, a higher ability to overcome obstacles in their recovery, and usually have better psychosocial functioning and well-being compared to those with low self-efficacy [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on chemotherapy patients found that better self-efficacy was associated with better quality of life and lower fatigue [ 11 ]. Confidence in one’s ability to manage oneself well is an important aspect of ongoing care [ 12 ]. Individuals with high self-efficacy after a stroke usually have greater confidence to participate in ADLs, a higher ability to overcome obstacles in their recovery, and usually have better psychosocial functioning and well-being compared to those with low self-efficacy [ 1 ].…”
Section: Introductionmentioning
confidence: 99%